Is the export led growth hypothesis valid for Malaysia? - Shahrin, A.R.; Shaharudin, R.S.; Abdull Mutalip, M.L (2008)
The development of Malaysia after 1970s is very much dependent on export sector as the engine of growth. However, some economists argue that dependence on export is among the factors that contribute to the financial crisis in 1997. Using aggregate production function and unconventional input as theoretical model, with data starting from 1988 until 2004, it is found that export led growth hypothesis for the period of study is rejected. The engine of growth for Malaysia for the period of study is caused by domestic market and not from foreign sector. This result challenges the superiority of outward oriented kind of policy for economic growth.